Stimuli-Responsive Nanogel/Microgel Hybrids as Targeted Drug Delivery Systems: A Comprehensive Review - Ghosh Majumdar, Amrita; Pany, Biswajit; Parua, Sankha Subhra; Mukherjee, Debdeepto; Panda, Agnihotri; Mohanty, Madhuchhanda; Das, Biswadeep; Si, Satyabrata; Mohanty, Priti S. (BioNanoScience, 2024)
In the recent years, smart stimuli-responsive nanogel-based smart systems are gaining a lot of interest in modern medicine. Global demand for controlled drug delivery systems is increasing day by day in order to overcome various challenges and reduce the toxic adverse effects of different chemotherapeutic drugs used in treatment of different diseases. Traditional drug delivery systems available in the market and used in different clinical trials are quite expensive and lack flexibility and efficiency to achieve desired results. In various biological applications, from cancer to neurological illnesses, nanogels constitute a cutting-edge platform for customizable drug release and targeted therapy. With the goal of streamlining the processes and offering cutting-edge nanomaterials, the design of these nanogels and their hybrid systems have been a crucial subject of study for researchers throughout the years. Our current review mainly focuses on synthesis of different stimuli-responsive smart nanogel systems, properties of nanogels in response to stimuli-responsive parameters like temperature, pH, redox potential, light, and magnetic field, and, finally, various applications of these smart delivery systems in response to these parameters which involve loading and unloading of drugs onto these systems and their mode of action. Graphical Abstract